Advanced Mechanical Science and Technology for the Industrial Revolution 4.0 (Springer Singapore, 2018)
This book includes more than 30 papers from the first FZU-OPU-NTOU Joint Symposium on Advanced Mechanical Science and Technology for the Industrial Revolution 4.0, held at Fuzhou University, China, in December 2016. The symposium was organized by Fuzhou University (FZU), Osaka Prefecture University (OPU) and National Taiwan Ocean University (NTOU). The authors include several professors from universities in China, Japan, and Taiwan as well as four distinguished invited professors from Canada, Korea, Japan, and Taiwan. The book covers all important aspects related to the 4.0 industrial revolution: robotics and mechatronics; sensors, measurements, and instrumentation; mechanical dynamics and controls; mechanical design; vehicle systems and technologies; fluid mechanics; monitoring and diagnosis, prognosis, and health management; advanced signal processing; and big data; all of which are subjects with great potential in the field of mechanical engineering.